PENINGKATAN KUALITAS PENYUSUNAN RPP MELALUI MONITORING DAN EVALUASI PELAKSANAAN PROGRAM SEKOLAH OLEH GURU DI SMPN 3 LUHAK NAN DUO - Imran, Imai (Jurnal Manajemen Pendidikan, 2018)
Based on the observations that the researchers did at the Luhak Nan Duo 3 Junior High School, it was found that the teacher's ability to develop RPP was still low. The purpose of this study was to describe and obtain information about the preparation of RPP by the teacher. This research is a school action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 10 teachers of Luhak Nan Duo Junior High School 3. Research data was collected using observation sheets. Data is analyzed using percentages. The results showed that Monitoring and Evaluation could improve the preparation of teacher RPP at Luhak Nan Duo Junior High School 3. This is evidenced by the evaluation and monitoring can improve the quality of the preparation of teacher RPP at Luhak Nan Duo 3 Junior High School from cycle I to cycle II. The average ability of teachers in improving the making of RPP in the first cycle was 51.39 with less categories, in the second cycle was 85.46 Good